Point‐by‐Point Radiofrequency Ablation Versus the Cryoballoon or a Novel Combined Approach: A Randomized Trial Comparing 3 Methods of Pulmonary Vein Isolation for Paroxysmal Atrial Fibrillation (The Cryo Versus RF Trial). (25th November 2015) - HUNTER, ROSS J.; BAKER, VICTORIA; FINLAY, MALCOLM C.; DUNCAN, EDWARD R.; LOVELL, MATTHEW J.; TAYEBJEE, MUZAHIR H.; ULLAH, WAQAS; SIDDIQUI, M. SHOAIB; M LEAN, AILSA; RICHMOND, LAURA; KIRKBY, CLAIRE; GINKS, MATTHEW R.; et al.
The CRYO Versus RF Trial: Introduction: Catheter ablation of paroxysmal AF using the Cryoballoon (CRYO) has yielded similar success rates to conventional wide encirclement using radiofrequency catheter ablation (RFCA), but randomized data are lacking. Pilot data suggested a high success rate with a combined approach (COMBINED) using wide encirclement with RFCA followed by 2 CRYO applications to each vein. We compared these 3 strategies in a randomized controlled trial. Methods and Results: Patients undergoing first time paroxysmal AF ablation were randomized to RFCA, CRYO, or COMBINED. Patients were followed up at 3, 6, and 12 months with 7 days of ambulatory ECG monitoring. Success was defined as freedom from arrhythmia without antiarrhythmic drugs after a single procedure. A total of 237 patients were randomized. Success at 1 year was achieved in 47% in the RFCA group, 67% in the CRYO group, and 76% in the COMBINED group (P < 0.001 for RFCA vs. CRYO, P<0.001 for RFCA vs. COMBINED, and P = 0.220 for CRYO vs. COMBINED). Procedure time was 211 (IQR 174–256) minutes for RFCA compared to 167 (136–202) minutes for CRYO and 278 (243–327) minutes for COMBINED (P < 0.001 for RFCA vs. COMBINED, RFCA vs. CRYO, and CRYO vs. COMBINED groups). Conclusions: Pulmonary vein isolation for paroxysmal AF is faster with CRYO and results in a higher single procedure success rate than conventional point by point RFCA. The COMBINED approach was not superior to CRYO alone.